1999
DOI: 10.1038/sj.onc.1203163
|View full text |Cite
|
Sign up to set email alerts
|

Serine phosphorylation of paxillin by heregulin-β1: role of p38 mitogen activated protein kinase

Abstract: The mechanisms through which heregulin (HRG) regulates the progression of breast cancer cells to a more invasive phenotype are currently unknown. Recently we have shown that HRG treatment of breast cancer cells leads to the formation of lamellipodia/ ®lopodia, and increased cell migration and invasiveness through the phosphatidylinositol 3-kinase (PI-3 kinase).Since the process of cell migration must involve changes in adhesion, we explored the potential HRG regulation of paxillin, a major cytoskeletal phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 50 publications
5
55
0
Order By: Relevance
“…Additionally, cells expressing this mutant paxillin exhibit a defect in spreading and protrusive abilities and migrate more actively [66,85,86,117]. Collectively, this would suggest that paxillin serine phosphorylation regulates the degradation status of the protein, which in turn, is important in the modulation of paxillin-dependent membrane dynamics affecting cell motility.…”
Section: Paxillin Serine/threonine Phosphorylationmentioning
confidence: 94%
See 2 more Smart Citations
“…Additionally, cells expressing this mutant paxillin exhibit a defect in spreading and protrusive abilities and migrate more actively [66,85,86,117]. Collectively, this would suggest that paxillin serine phosphorylation regulates the degradation status of the protein, which in turn, is important in the modulation of paxillin-dependent membrane dynamics affecting cell motility.…”
Section: Paxillin Serine/threonine Phosphorylationmentioning
confidence: 94%
“…Whereas tyrosine phosphorylation of paxillin by FAK/Src is well documented, much less is known of the consequences of paxillin serine phosphorylation or the kinases that are involved [32,47,66,86,117]. Like tyrosine phosphorylation, paxillin serine/threonine phosphorylation is induced by a variety of stimuli: for example, cellular activation via integrin ligation has been documented to result in phosphorylation of S188/190 [47].…”
Section: Paxillin Serine/threonine Phosphorylationmentioning
confidence: 99%
See 1 more Smart Citation
“…[30][31][32] Although Smad2/3 signaling is relatively specific to the binding of ligands of the TGFb/activin family to cell surface receptors, investigators are discovering that MAPKs (p42/p44 Erk1/2, JNK, or p38MAPK) phosphorylate specific sites in the middle linker region of Smad2/3, sites that are distinct from the C-terminus that is phosphorylated by the TGFb II receptor (Figure 2). [33][34][35][36] Thus, ligands capable of activating MAPKs potentially modulate Smad signaling induced by TGFb. It has recently been demonstrated that p38MAPK activate phosphorylation of Smad3 in the middle linker region, which enhances Smad3/4 complex formation and nuclear translocation, 37 consistent with our finding of diminished Smad3/4 reporter gene activity in the presence of a p38MAPK inhibitor.…”
Section: Tgfb Signal Transductionmentioning
confidence: 99%
“…16 The p38 MAP kinase-dependent signal transduction pathway(s) plays a role in serine phosphorylation and disassembly of paxillin. 17 Expression of VEGF, a multifunctional cytokine, is crucial in angiogenesis during the development of cancer and correlates with disease recurrence in patients with early gastric carcinoma. 18 p38 MAP kinase activation by VEGF mediates actin reorganization and cell migration in human endothelial cells.…”
Section: Genes Related To Extracellular Matrixmentioning
confidence: 99%